1995
DOI: 10.1103/physrevd.52.6157
|View full text |Cite
|
Sign up to set email alerts
|

Exotic nonsupersymmetric gauge dynamics from supersymmetric QCD

Abstract: We extend Seiberg's qualitative picture of the behavior of supersymmetric QCD to nonsupersymmetric models by adding soft supersymmetry breaking terms. In this way, we recover the standard vacuum of QCD with N f flavors and N c colors when N f < N c . However, for N f ≥ N c , we find new exotic statesnew vacua with spontaneously broken baryon number for N f = N c , and a vacuum state with unbroken chiral symmetry for N f > N c . These exotic vacua contain massless composite fermions and, in some cases, dynamica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
194
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(200 citation statements)
references
References 33 publications
(95 reference statements)
6
194
0
Order By: Relevance
“…Since so much information follows from the solution of the pure N = 2 one would like to be able to break N = 2 supersymmetry down to N = 0 in terms of a collection of soft breaking terms preserving all the holomorphy and monodromy properties which were crucial to determine the solutions in [3,4]. This was begun in [14,15] (for N = 1 similar soft breaking analysis was done in [12,13] to understand the implications of the non-perturbative superpotentials obtained by Seiberg and collaborators [1,2] in the absence of supersymmetry). In this paper we study the most general soft breakings in N = 2 QCD-like theories including massive hypermultiplets.…”
Section: Introductionmentioning
confidence: 99%
“…Since so much information follows from the solution of the pure N = 2 one would like to be able to break N = 2 supersymmetry down to N = 0 in terms of a collection of soft breaking terms preserving all the holomorphy and monodromy properties which were crucial to determine the solutions in [3,4]. This was begun in [14,15] (for N = 1 similar soft breaking analysis was done in [12,13] to understand the implications of the non-perturbative superpotentials obtained by Seiberg and collaborators [1,2] in the absence of supersymmetry). In this paper we study the most general soft breakings in N = 2 QCD-like theories including massive hypermultiplets.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of soft supersymmetry breaking in N = 1 theories has been known for some time [8]. In [9,10] soft breaking terms are used to explore N = 1 supersymmetric QCD (SQCD) with gauge group SU(N c ) and N f flavours of quarks, and to extrapolate the exact results in [6] concerning the superpotential and the phase structure of these theories in the absence of supersymmetry. This leads to expected and unexpected predictions for non-supersymmetric theories which may eventually be accessible to lattice computations.…”
Section: Introductionmentioning
confidence: 99%
“…Aharony et al first studied such deformations and found various interesting vacua which may or may not be connected to the QCD vacuum [4]. Later, Arkani-Hamed and Rattazzi have established relations among the soft terms in electric and magnetic descriptions [5].…”
Section: Evading the Vafa-witten Theoremmentioning
confidence: 99%